TJNPR 2020
DOI: 10.26538/tjnpr/v4i7.5
|View full text |Cite
|
Sign up to set email alerts
|

Neurobehavioural Enhancement in Scopolamine Hydrobromide-Induced Alzheimer Type Cognitive Dysfunction in Rats Following Administration of Ethanol Seed Extract of Telfairia occidentalis (Hook.f.) Cucurbitaceae

Abstract: Cognitive dysfunction including Alzheimer's disease (AD) and other neurodegenerative disorders are major health problem which are debilitating in nature. 1,2 The global prevalence of dementia in adults aged >60 years ranged from 5 to 7% with AD as the most common type followed by vascular dementia. 3,4 There are scarce and conflicting reports on the prevalence of dementia with far-reaching implications on the public health policies in the sub-Saharan Africa. 3,5,6 In Nigeria, incidence of dementia and Alzheime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…This result showed that the treated groups showed intact spatial working memory. This means that the extracts possess the potentials that can enhance learning and memory in rats, however, this is in line with Eru et al, Rabiei et 13,15,16,50,52,53,61,13,54,57…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…This result showed that the treated groups showed intact spatial working memory. This means that the extracts possess the potentials that can enhance learning and memory in rats, however, this is in line with Eru et al, Rabiei et 13,15,16,50,52,53,61,13,54,57…”
Section: Resultssupporting
confidence: 76%
“…31,32,58,8 It diminishes cerebral blood flow due to cholinergic hypofunction. 58,59 This pharmacological agent triggers oxidants, causes free oxidant injury and increases brain malondealdehyde (MDA) levels and depletion of antioxidant status in a scopolamine-treated group 23,13,28 and has been proven to elevate the status of amyloid precursor proteins and tau proteins. Scopolamine treatment leads to marked histological distortions in the cerebral cortex including neuronal degeneration 3 and new drugs for Alzheimer's disease were evaluated using scopolamine induced dementia humans and animals.…”
Section: Introductionmentioning
confidence: 99%
“…The ameliorative potentials of the aqueous fruit extract may be due to its antioxidant properties which is in line with studies where T. Occidentalis has the potential to ameliorate hippocampal microstructure as well as enhance learning and memory in scopolamine hydrobromide-induced Alzheimer's type cognitive dysfunction in rats and this was also attributed to its high antioxidant components. 32,33…”
Section: Resultsmentioning
confidence: 99%
“…The plant is characterised with pharmacological activities such as antioxidants, antidiabetic, antibacterial, anti-inflammatory and antifungal effects (Nkosi et al, 2006). Pumpkin seeds have been documented to possess neuroprotective effects and enhanced learning and memory (Eru et al, 2020;2021).…”
Section: Introductionmentioning
confidence: 99%